The Handbook of Child and Adolescent Clinical Psychology / A Contextual Approach - Carr Alan (Routledge - Taylor & Francis Group, 2006)
This book does an admirable job in providing immensely practical approaches for the assessment and treatment of mental health problems in young people, whilst also being critically and constructively informative on the findings of research and the claims of theories. Acknowledgements, Frameworks of Practice, Normal Development, Influences on Problem Development, Classification and Epidemiology and Treatment Effectiveness, The Consultation Process and Intake Interviews, Report Writing, Problems of Infancy and Early Childhood, Sleep Problems, Toileting Problems, Intellectual and Learning and Communication Disabilities, Autism and Pervasive Developmental Disorders, Problems of Middle Childhood, Conduct Problems, Attention and Over-Activity Problems, Fear and Anxiety Problems, Repeatition Problems, Somatic Problems, Problems in Adolescence, Drug Abuse, Mood Problems, Anorexia and Bulimia Nervosa, Schizophrenia, Child Abuse, Physical Child Abuse, Emotional Abuse and Neglect, Sexual Abuse, Adjustment to Major Life Transitions, Foster Care, Separation and Divorce, Grief and Bereavement, References, Index.